A Novel Intracellular Isoform of Matrix Metalloproteinase-2 Induced by Oxidative Stress Activates Innate Immunity - Lovett, David H.; Mahimkar, Rajeev; Raffai, Robert L.; Cape, Leslie; Maklashina, Elena; Cecchini, Gary; Karliner, Joel S. (PLOS ONE, 2012)
Background Experimental and clinical evidence has pinpointed a critical role for matrix metalloproteinase-2 (MMP-2) in ischemic ventricular remodeling and systolic heart failure. Prior studies have demonstrated that transgenic expression of the full-length, 68 kDa, secreted form of MMP-2 induces severe systolic failure. These mice also had unexpected and severe mitochondrial structural abnormalities and dysfunction. We hypothesized that an additional intracellular isoform of MMP-2, which affects mitochondrial function is induced under conditions of systolic failure-associated oxidative stress. Methodology and Principal Findings Western blots of cardiac mitochondria from the full length MMP-2 transgenics, ageing mice and a model of accelerated atherogenesis revealed a smaller 65 kDa MMP-2 isoform. Cultured cardiomyoblasts subjected to transient oxidative stress generated the 65 kDa MMP-2 isoform. The 65 kDa MMP-2 isoform was also induced by hypoxic culture of cardiomyoblasts. Genomic database analysis of the MMP-2 gene mapped transcriptional start sites and RNA transcripts induced by hypoxia or epigenetic modifiers within the first intron of the MMP-2 gene. Translation of these transcripts yields a 65 kDa N-terminal truncated isoform beginning at M77, thereby deleting the signal sequence and inhibitory prodomain. Cellular trafficking studies demonstrated that the 65 kDa MMP-2 isoform is not secreted and is present in cytosolic and mitochondrial fractions, while the full length 68 kDa isoform was found only in the extracellular space. Expression of the 65 kDa MMP-2 isoform induced mitochondrial-nuclear stress signaling with activation of the pro-inflammatory NF-κB, NFAT and IRF transcriptional pathways. By microarray, the 65 kDa MMP-2 induces an innate immunity transcriptome, including viral stress response genes, innate immunity transcription factor IRF7, chemokines and pro-apoptosis genes. Conclusion A novel N-terminal truncated intracellular isoform of MMP-2 is induced by oxidative stress. This isoform initiates a primary innate immune response that may contribute to progressive cardiac dysfunction in the setting of ischemia and systolic failure.